Prenatal Diagnosis of a Segmental Small Bowel Volvulus with Threatened Premature Labor - Barbara Monard; Nicolas Mottet; Rajeev Ramanah; Didier Riethmuller (Case Reports in Obstetrics and Gynecology)
Fetal primary small bowel volvulus is extremely rare but represents a serious life-threatening condition needing emergency neonatal surgical management to avoid severe digestive consequences. We report a case of primary small bowel volvulus with meconium peritonitis prenatally diagnosed at 27 weeks and 4 days of gestation during threatened premature labor with reduced fetal movements. Ultrasound showed a small bowel mildly dilated with thickened and hyperechogenic intestinal wall, with a typical whirlpool configuration. Normal fetal development allowed continuation of pregnancy with ultrasound follow-up. Induction of labor was decided at 37 weeks and 2 days of gestation because of a significant aggravation of intestinal dilatation appearing more extensive with peritoneal calcifications leading to the suspicion of meconium peritonitis, associated with reduced fetal movements and reduced fetal heart rate variability, for neonatal surgical management with a good outcome.